Discrimination of genotype and geographical origin of black rice grown in Brazil by LC-MS analysis of phenolics. (1st August 2019) - Dittgen, Caroline Lambrecht; Hoffmann, Jessica Fernanda; Chaves, Fábio Clasen; Rombaldi, Cesar Valmor; Filho, José Manoel Colombari; Vanier, Nathan Levien
Highlights: PCA and PLS-DA data sets showed distinction among genotypes and locations. Quercetin-3- O -glucoside and vanillic acid were relevant for discriminating genotypes. Hesperetin, vanillic acid, quercetion-3- O -glucoside, and p -coumaric acid were the relevant for discriminating locations. Chalkiness occurrence in AE 153045 elite-line at one location was associated to latitude and wind conditions. Growing location influenced cyanidin-3- O -glucoside and peonidin-3- O -glucoside contents. Abstract: Physicochemical properties, cooking time, and phenolics profile of two black rice genotypes grown at six different locations in Brazil were determined. The cultivar IAC 600 and the elite-line AE 153045 were used. The main growing locations for black rice were considered, as follows: Alegrete (ALG), Capão do Leão (CPL), Guaratinguetá (GUA), Roseira (ROS), Santa Vitória do Palmar (SVP), and Taubaté (TBT). Principal component analysis (PCA) and supervised partial least squares-discriminant analysis (PLS-DA) from liquid chromatography-mass spectrometry (LC-MS) data sets showed distinction among genotypes and locations. Quercetin-3- O -glucoside and vanillic acid were the most relevant compounds for discriminating genotypes. SVP location provided the most distinctive black rice, with greater total phenolics content. Characteristics of black rice from SVP location were associated to effects of latitude and wind conditions. Hesperetin, vanillic acid, quercetion-3-O-glucoside, and p -coumaric acid were the most relevant compounds for discriminating locations.